2019
DOI: 10.5114/polp.2019.86443
|View full text |Cite
|
Sign up to set email alerts
|

Interactive video games to promote physical activity among healthy children and youths

Abstract: Physical activity is crucial in reducing the risk of civilisation diseases: type 2 diabetes, hypertension, obesity, osteoporosis, cancer, and depression. An adequate level of physical activity during childhood prevents the development of early atherosclerotic lesions, which result from obesity, hypertension, and dyslipidaemia, frequently appearing amongst children. Most children do not meet the basic physical activity guidelines. Children spend most of their time in a sitting position, which reduces their dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Previous research has shown that active video games may be an effective method of promoting independent physical activity and limiting the time spent in a sedentary position during inactive video games [ 10 , 28 ]. Studies comparing exergames with other type of physical exercise found that active games increased energy expenditure, corresponding to mild, moderate, or even intensive physical activity levels, and improved physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that active video games may be an effective method of promoting independent physical activity and limiting the time spent in a sedentary position during inactive video games [ 10 , 28 ]. Studies comparing exergames with other type of physical exercise found that active games increased energy expenditure, corresponding to mild, moderate, or even intensive physical activity levels, and improved physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing exergames with other type of physical exercise found that active games increased energy expenditure, corresponding to mild, moderate, or even intensive physical activity levels, and improved physiological parameters. Exergames may support sedentary individuals to become more active, especially those experiencing difficulties or embarrassing when practicing exercise in public, as though youth with obesity [ 28 ]. However, their exclusive role in improving weight status as a consequence of this increase in energy expenditure has not been defined yet.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Hwang et al (2013) demonstrates that instructional computer games have a positive impact on children's academic performance and their attitudes towards learning. Further investigation conducted by Shoesmith et al (2019) and Kowaluk and Woźniewski (2019) emphasizes the efficacy of interactive games in enhancing children's physical activity levels and digital literacy skills.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of exergaming technology has numerous benefits for physical health, resulting in significantly higher physical activity (PA) compared to sedentary behavior [ 1 , 2 ]. This is especially true for children and adolescents in home-based environments [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%